The Effect of Endotoxin on the Intestinal Mucus Layer in Non- and Post-pregnancy Mice - Yan, Dujian; Qiang, Yuyun; Tian, Tian; Lu, Dezhang; Wu, Chenchen (Frontiers in Veterinary Science, 2022)
The intestine is the most extensive storage organ of bacteria and endotoxins, and the mucosal immune system is the first barrier of the intestine. Mucin-2 (MUC2) is the major component of the mucus layers. In this study, we explored whether MUC2 plays a role in how lipopolysaccharide (LPS) invades the fetus from the gut to the uterus in pregnant mice. The results showed that the LPS levels of the ileum, colon, and uterus were significantly increased, and the content of secretory IgA (sIgA) in the ileum, colon, and uterus tissues was significantly decreased in the LPS(+) group on the 35th day after LPS treatment. On the 16th day of pregnancy, compared with the LPS(-) group, the level of ileum LPS was significantly decreased, and the content of LPS in the fetus was significantly increased in the LPS(+) group. The sIgA content in the fetus was significantly decreased in the uterus and placenta. The expression of MUC2 in the uterus, ileum, and colon was increased significantly in the LPS(+) group, especially in the uterus. It is suggested that endotoxins accumulate in the uterus during non-pregnancy. The high expression of MUC2 in the uterus can prevent LPS from translocating into uterine tissue. After pregnancy, MUC2 still protects uterine tissue, allowing a large amount of LPS to enter the fetal body through blood circulation. Therefore, the level of sIgA significantly decreased, resulting in a decline in fetal innate immune function.